(untitled) (Research, Society and Development, 2023)
This analysis aims to evaluate the quality of the lunch menus of servers at the Hospital Food and Nutrition Unit in the municipality of Jequié-BA. Methodology: the AQPC method by Veiros and Proença (2003) was applied to the menus in the second half of 2022, totaling 42 days of analysis. Positive aspects of leafy vegetables and fruits were observed, and negative aspects related to the monotony of colors, foods rich in sulfur, fatty meats, sweets, fried foods and fried foods associated with sweets and classified according to the frequency of occurrence. Results: according to the verification of the collected data, the offer of fruits presented 100% of presence in the diet of diners (“great”), and 78.6% of leafy vegetables (“good”). Regarding the monotony of colors 47.6%, on foods rich in sulfur 45.2%, isolated fried foods 50% and fried foods associated with sweets 50%, categorized as “regular”. Regarding the appearance of 54.8% of fatty meats, this was indicated as “bad” and the presence of sweets, “terrible”. Final considerations: in this way, the findings of the unfavorable configuration offer indications of the need for menu adjustments by the nutritionist technical professional, in order to improve the presentation of the types of preparations manipulated, and above all, to influence the adoption of good adequate eating habits for this to occur. better nutritional intake of hospital employees.